Breathing in the megacity: photographic atmospheres, polluted airs. (2nd January 2021) - van Aitken, John; Brake, Jane
Abstract : Written from an artists' perspective this article considers photography's engagement with the polluted meteorological atmosphere and its constitutive role in the production of megacity imaginaries. On visits to Shanghai between 2017 and 2019 we made elevated views of the megacity, generated field notes, poetics, breathed the air and became unwell. We draw on the work of Gernot Böhme and Peter Sloterdijk amongst others to initiate a new and pressing discussion: what happens when we think of photography and breathing together?